Analisis Estimasi Biaya Pembuatan Perangkat Lunak Menggunakan Metode COCOMO II di Inagata Technosmith (Studi Kasus : Sistem Informasi Monitoring dan Evaluasi Penerimaan Beasiswa Santri Berprestasi UIN Malang) - Della Eko Damayanti; Suprapto Suprapto; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
In conducting a software project, the success of the project should begin with a proper planning. If the planning is considered as bad, it will cause the failure of the project. One of the example of failure projects takes place on the time swelling of the Time swelling can lead to the swelling of the project cost. One of the project planning phase is the project cost estimation. Project cost estimation constitutes time, cost and number estimation of employees working on the project. The cost estimation of this research uses COCOMO II method. COCOMO II method provide a cost estimation technique which aims to determine how long is the process of software development and the number of employees needed to finish the software project. To describe the characteristics of the project, COCOMO II method uses Scale Driver and Effort Multipliers questionnaires which are distributed to the entire project team. To illustrate the complexity of the system that will be done, the value of Unadjusted Function Point is used in each process of Monitoring Information System and Evaluation of Achieved-Student Scholarship Enrollment of UIN Malang which are obtained from Data Flow Diagram analysis. The research result is the cost estimation (time, cost, number of employees) to finish the Monitoring Information System project and Evaluation of Achieved-Student Scholarship Enrollment of UIN Malang